Systems Analysis of the Functional Condition Children with Neurosensory Bradyacuasia - I. V. Dudarev; G. Sh. Gafijatullina; N. A. Alekseeva; E. V. Trofimova (Медицинский вестник Юга России, 2011)
Purpose: The psycho-physiological features and anthrop-somatic-viceroy parameters in children with neurosensory bradyacuasia (NSB) were investigated.Materials and Methods: It is spent comparative research of boys with НСТ, divided into age subgroups: 7-10 years, 11-13 and 14-16 years. Were executed audio-logic, anthropometrical, physical analyses, psychological testing for revealing of verbal and nonverbal characteristics of intellectual development, it is registered electroencephalogram (EEG) and the evoked potentials.Results: In each group prominent features of the inter-central mutual relations in a brain cortex are revealed. It is established that the condition intra- and inter-hemispheres’ integration and character of spectral density of ranges EEG capacity can represent itself as functional criterion of development NSB. At acquired NSB age-related characteristics of the alpha - rhythm power is not boosted, at inherent - the level of left-side coherent links increases. The decrease of amplitude of visual evoked potential positive components can be connected to failure the hard of hearing children notice function.Summary: The data of the factorial analysis of set anthropometrical, physical and viceroy indicators, parameters of bioelectric activity of a brain, can be diagnostic criteria of anthrop-somatic-viceroy continuum components of a studied pathology.